A COMPARATIVE ANALYSIS OF THE GRI G3.1 AND THE GRI G4 EXPOSURE DRAFT - Lamborghini, Fara Laynds; Sukoharsono, Eko Ganis (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Social responsibility accounting is a concept explains that organizations have a responsibility towards customers, employees, shareholders, communities and the environment in all aspects of company operations. Therefore, there is guidelines guidance for the preparation of sustainability report in proving social responsibility to the stakeholders and shareholders, such as the Global Reporting Initiative (GRI). GRI itself has latest two versions. First, GRI G3.1 and the last one is GRI G4-Exposure Draft which is going to launch in the mid of 2013. It is expected to be able to examine the effectiveness of company or institution in using guideline of GRI G4 which is going to launch in 2013 in reporting the sustainability performance. It could be done by analyzing the advantages and find the lack of information within standards, the points that have not included yet, and try to give inputs and advices for the standard development. Â Keywords:Â Â Social Responsibility Accounting, Sustainability Report, Global Report Initiative (GRI), GRI G3.1, GRI G4-Exposures Draft